2014
DOI: 10.1371/journal.pcbi.1003910
|View full text |Cite
|
Sign up to set email alerts
|

Putting Theory to the Test: Which Regulatory Mechanisms Can Drive Realistic Growth of a Root?

Abstract: In recent years there has been a strong development of computational approaches to mechanistically understand organ growth regulation in plants. In this study, simulation methods were used to explore which regulatory mechanisms can lead to realistic output at the cell and whole organ scale and which other possibilities must be discarded as they result in cellular patterns and kinematic characteristics that are not consistent with experimental observations for the Arabidopsis thaliana primary root. To aid in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 77 publications
(135 reference statements)
4
41
0
1
Order By: Relevance
“…The importance of apical meristem activity in determining growth rate has been highlighted (Beemster and Baskin, 1998), and its sensitivity to water deficit has been shown in maize and poplar roots (Fraser et al , 1990; Sacks et al , 1997; Bizet et al , 2015 b ). The balance between proliferation and elongation processes, as well as their underlying molecular control, is a current research focus (Tardieu et al , 2011; Baskin, 2013; De Vos et al , 2014). A gene expression map at high spatial resolution has led to better knowledge of the transcriptional circuits linked to root development in Arabidopsis thaliana (Birnbaum et al , 2003; Brady et al , 2007; Iyer-Pascuzzi et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of apical meristem activity in determining growth rate has been highlighted (Beemster and Baskin, 1998), and its sensitivity to water deficit has been shown in maize and poplar roots (Fraser et al , 1990; Sacks et al , 1997; Bizet et al , 2015 b ). The balance between proliferation and elongation processes, as well as their underlying molecular control, is a current research focus (Tardieu et al , 2011; Baskin, 2013; De Vos et al , 2014). A gene expression map at high spatial resolution has led to better knowledge of the transcriptional circuits linked to root development in Arabidopsis thaliana (Birnbaum et al , 2003; Brady et al , 2007; Iyer-Pascuzzi et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the model of Vos et al (2014), vertices are constrained to move only parallel to the longitudinal axis of the root. This allows for the anisotropic elastic-plastic properties of the cell-wall material to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Vos et al (2014) also considered such a growth function (for the cell target volume) as one of the options in the vertex-based simulation of Arabidopsis root growth. At the same time, in a number of studies (Barlow, 1969; van der Weele et al, 2003) based on experimental data on cell length profiles along the growth axis of the Arabidopsis root, the authors suggested a smooth non-linear growth function for the cell length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…how hormonal crosstalk influences the size of the root meristem (de Vos et al, 2014); and how this crosstalk can lead to the emergence of gene expression patterns (Liu et al 2010;Moore et al 2015a).…”
Section: Discussionmentioning
confidence: 99%